- #1

phospho

- 251

- 0

in an earlier part of the equation we had to prove that a tangent to the a hyperbola in the form of [itex] \frac{x^2}{a^2} - \frac{y^2}{b^2} = 1 [/itex] is in the form of [itex] a^2m^2 = b^2 + c^2 [/itex] where the tangent is in the form of y = mx + c

so I differentiated with respect to x and got

[tex] \dfrac{dy}{dx} = \dfrac{16x}{25y} [/tex]

subbing in the values of x and y I get the value of dy/dx to be 4/25

dy/dx is the gradient of the tangent so subbing that into the equation [itex] a^2m^2 = b^2 + c^2 [/itex] as well as the values for a^2 and b^2 I can't get any real values for the constant, c so I'm not sure where I've gone wrong.